ئەدای پيشەيى لە ڕوانگەى تيۆرە زانستييەكانەوە توێژينەوەيەكى تيۆرى شيكارييە لە ديدێكى سۆسيۆلۆجييەوە - عبدالله, پ د.ئاسۆ إبراهیم; إبراهیم, م.م لانە ئاراس (Sulaimani Journal for Humanities, 2023)
Professional performance is one of the modern concepts, as researchers paid attention to it in their studies and in several fields, including management, economics, education, sociology, psychology and other fields.The performance of its cadres and employees in order to reach its material, moral and spiritual goals and objectives, and all of this depends on the amount of activities, competencies and skills exerted by the employees in order to reach societal goals, as a key to the development and evolution that all countries seeks, in this context we present in our research ideas and scientific proposals related The concept of professional performance and identifying its components and dimensions and the factors influencing them and the theoretical approaches explaining the professional performance from a sociological perspective.
Keywords: Performance; professional performance